Analysis of velocity and temperature fields inside an air solar collector – A numerical approach. Issue 1 (May 2021) - Teodosiu, C; Sima, C; Bode, F; Croitoru, C
Abstract: The numerical study is performed on a glazed transpired solar collector, investigating the effect of different distances between the glazing and the absorber (30 and 50 mm) for different airflow rates. The results show that the best solution among the tested configurations is using the 30 mm distance between the glazing and absorber, no matter what the air flow rate is. The efficiency of the glazed transpired solar collector (GTC) in this case is between 50%-61% for the range of airflow rates studied and higher with around 15% compared to configurations with larger distance between the glazing and absorber. The purpose of this study is to prove the efficiency increase due to pass-through elements disposals complementary with the passive components implementation, underlining the benefit of passive solar systems.